2014
DOI: 10.3233/jad-131322
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Amplitude of Low-Frequency Fluctuations of Intrinsic Brain Activity in Alzheimer's Disease

Abstract: We used resting-state functional magnetic resonance imaging to measure the amplitude of low-frequency fluctuations (ALFF) of intrinsic brain activity in 23 patients with moderate Alzheimer's disease (AD) and 27 age- and gender-matched healthy controls. Two different frequency bands were analyzed (slow-5:0.01-0.027 Hz; slow-4:0.027-0.073 Hz). In many brain regions, widespread ALFF differences between the two frequency bands were observed, including predominantly the posterior cingulate cortex/precuneus (PCC/PCu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
90
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 42 publications
7
90
5
Order By: Relevance
“…Interestingly, however, the cognitive scores did not correlate with ALFF values at all, contradicting previous studies Liu et al, 2014a;Wang et al, 2011), but only with the connectivity values instead. One possible explanation for our results is that PCC ALFF values are altered in mild AD patients, either due to abnormal amyloid deposition, synaptic dysfunction, or metabolic changes, which leads to a disconnection with the parietal and frontal regions (and the latter causes cognitive problems).…”
Section: Discussioncontrasting
confidence: 77%
“…Interestingly, however, the cognitive scores did not correlate with ALFF values at all, contradicting previous studies Liu et al, 2014a;Wang et al, 2011), but only with the connectivity values instead. One possible explanation for our results is that PCC ALFF values are altered in mild AD patients, either due to abnormal amyloid deposition, synaptic dysfunction, or metabolic changes, which leads to a disconnection with the parietal and frontal regions (and the latter causes cognitive problems).…”
Section: Discussioncontrasting
confidence: 77%
“…Such a depression in the amplitude of those frequencies may have not only contributed, in part, to the appearance of the observed shifted peaks but also contributed to the reduced network coherence and synchronicity, allowing for long-distance communication between nodes of a network. In agreement with data presented in previous studies in aging-related pathologies (Han et al, 2011;Liu et al, 2014), these changes and differences observed in the slow-5 band of the resting state are indicative of a vulnerability of the slow-5 oscillations to disruption induced by the progression of normal aging and by the onset of an ischemic stroke.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the amplitude of LFF (ALFF) may indicate the amplitude of regional spontaneous neuronal activity [27]. Moreover, a number of R-fMRI studies have utilized the ALFF metric to study functional alterations in the hippocampus in patients with AD and/or mild cognitive impairment [21,26,[30][31][32][33][34]. Crosscorrelation coefficient of spontaneous low-frequency (COSLOF) is an index that measures mean connectivity within a brain region.…”
Section: Introductionmentioning
confidence: 99%